Intraplaque High-Intensity Signal on 3D Time-of-Flight MR Angiography Is Strongly Associated with Symptomatic Carotid Artery Stenosis - Gupta, A.; Baradaran, H.; Kamel, H.; Mangla, A.; Pandya, A.; Fodera, V.; Dunning, A.; Sanelli, P.C. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Intraplaque hemorrhage in carotid artery atherosclerotic plaque has been shown to be a marker of risk, associated with prior and future ischemic events, and has been associated with regions of intraplaque high-intensity signal on 3D-TOF MRA. We assessed the association of intraplaque high-intensity signal determined on 3D-TOF MRA with the incidence of prior ipsilateral stroke or TIA. MATERIALS AND METHODS: We assessed intraplaque hemorrhage by evaluating for intraplaque high-intensity signal adapting a recently validated technique on 3D-TOF source images in participants with high-grade (≥70%) extracranial carotid stenosis. Logistic regression analyses were used to assess the strength of association between the presence of intraplaque high-intensity signal on routine MRA sequences and prior stroke or TIA. RESULTS: Intraplaque high-intensity signal was present in 22 (41.5%) of 53 carotid arteries studied in 51 patients. Ipsilateral ischemic events occurred in 15 (68.1%) of 22 in the intraplaque high-intensity signal–positive group (10 strokes, 5 TIAs) and in 4 (12.9%) of 31 in the intraplaque high-intensity signal–negative group (3 strokes, 1 TIA). Ischemic events occurred within the 6-month period preceding imaging in 18 (94.7%) of 19 cases. The univariate odds ratio of the association of intraplaque high-intensity signal with any prior ischemic event was 14.5 (95% CI, 3.6–57.6), and the multivariate age- and sex-adjusted odds ratio was 14.2 (95% CI, 3.3–60.5). The association remained present across 1.5T and 3T magnet field strengths. CONCLUSIONS: Intraplaque high-intensity signal determined from MRA sequences already in place to measure luminal stenosis is strongly associated with prior ipsilateral ischemic events. Prospective validation of these findings to predict outcome in carotid artery stenosis could provide a valuable and widely accessible stroke risk stratification tool. IHISintraplaque high-intensity signalIPHintraplaque hemorrhage